2023
DOI: 10.3389/fphar.2023.1219866
|View full text |Cite
|
Sign up to set email alerts
|

Chemical characterization and metabolic profiling of Xiao-Er-An-Shen Decoction by UPLC-QTOF/MS

Ruipei Yang,
Lifang Wei,
Jie Wang
et al.

Abstract: Background: Xiao-Er-An-Shen decoction (XEASD), a TCM formula composed of sixteen Chinese medicinal herbs, has been used to alleviate tic disorders (TD) in clinical practice for many years. However, the chemical basis underlying the therapeutic effects of XEASD in the treatment of TD remains unknown.Purpose: The present study aimed to determine the major chemical components of XEASD and its prototype compounds and metabolites in mice biological samples.Methods: The chemical constituents in XEASD were identified… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 45 publications
0
1
0
Order By: Relevance
“…UHPLC-QTOF-MS E was widely used in the research field of herbs, which can provide us with massive data information reflecting chemical components. In UHPLC-QTOF-MS E analysis of ASR and APR, we explored the sample pretreatment methods such as extraction of solvents methanol, ethyl acetate, and water under ultrasound or heating reflux based on the principle of obtaining more mass spectrometry data information and convenient operation. The results found that the mass spectrometry data obtained when methanol was used as an extraction solvent was significantly higher than that of water, and ethyl acetate was used as a solvent.…”
Section: Resultsmentioning
confidence: 99%
“…UHPLC-QTOF-MS E was widely used in the research field of herbs, which can provide us with massive data information reflecting chemical components. In UHPLC-QTOF-MS E analysis of ASR and APR, we explored the sample pretreatment methods such as extraction of solvents methanol, ethyl acetate, and water under ultrasound or heating reflux based on the principle of obtaining more mass spectrometry data information and convenient operation. The results found that the mass spectrometry data obtained when methanol was used as an extraction solvent was significantly higher than that of water, and ethyl acetate was used as a solvent.…”
Section: Resultsmentioning
confidence: 99%
“…The first step was on-line data acquisition. It was performed in the full scan mode and depended on multiple mass defect filtering (MMDF) and dynamic background subtraction (DBS) techniques to capture all the probable metabolites ( Zhang et al, 2017 ; Yang et al, 2023 ). The OS software (version 1.6.1, Applied Biosystems/Sciex, CA, United States) was used for the data acquisition.…”
Section: Methodsmentioning
confidence: 99%